Phenotypic and Genotypic Characterization of Staphylococcus aureus Strains from Italian Dairy Products - Stefano Morandi; Milena Brasca; Cristian Andrighetto; Angiolella Lombardi; Roberta Lodi (International Journal of Microbiology)
Staphylococcus aureus is a known major cause of foodborne illnesses, and milk and dairy products are often contaminated by enterotoxigenic strains of this bacterium. In the present study, 122 S. aureus isolates collected from different dairy products were characterised by phenotypic properties, by the distribution of genes encoding staphylococcal enterotoxins (sea, sec, sed, seg, seh, sei, sej, and sel) and by randomly amplified polymorphic DNA PCR (RAPD-PCR). Moreover, strain resistance to vancomycin and methicillin (oxacillin) was studied. The differences in the RAPD-PCR profiles obtained with the primers M13 and AP4 revealed the presence of a great genetic heterogeneity among the different S. aureus strains. Using the primer AP4 and M13, eight groups were distinguished by RAPD-PCR cluster analysis, although, except in few cases, it was not possible to correlate the isolates of different animal species (cow or ovine) with the presence of se genes. None of the isolates showed resistance to vancomycin or methicillin.